2014
DOI: 10.3390/ijms15034104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interferon-Alpha Combined with Chemo (Radio) Therapy on Immunological Parameters in Pancreatic Adenocarcinoma

Abstract: Prognosis of patients with carcinoma of the exocrine pancreas is particularly poor. A combination of chemotherapy with immunotherapy could be an option for treatment of pancreatic cancer. The aim of this study was to perform an immunomonitoring of 17 patients with pancreatic cancer from the CapRI-2 study, and tumor-bearing mice treated with combination of chemo (radio) therapies with interferon-2α. Low doses of interferon-2α led to a decrease in total leukocyte and an increase in monocyte counts. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Earlier, we have showed that in human PDAC cells, the phosphorylation of CREB, ERK1/2, GSK−3, JNK1, JNK2/3, and P38 can be affected by DT3 (Karakhanova et al 2014b). Now, we have analyzed the impact of DT3 on in vivo phosphorylation of these signaling proteins in tumors of PDAC-bearing mice after their treatment with DT3 (Fig.…”
Section: Dt3 Decreases Phosphorylation Of Gsk−3 P38 and Creb In Murmentioning
confidence: 97%
See 4 more Smart Citations
“…Earlier, we have showed that in human PDAC cells, the phosphorylation of CREB, ERK1/2, GSK−3, JNK1, JNK2/3, and P38 can be affected by DT3 (Karakhanova et al 2014b). Now, we have analyzed the impact of DT3 on in vivo phosphorylation of these signaling proteins in tumors of PDAC-bearing mice after their treatment with DT3 (Fig.…”
Section: Dt3 Decreases Phosphorylation Of Gsk−3 P38 and Creb In Murmentioning
confidence: 97%
“…Cell viability after DT3 treatment was analyzed both with a EZ4U Kit (Biomedica, Austria) and with a ApoTox-Glo™ Triplex Assay Kit (Promega, USA), and proliferation was assessed with a BrdU Cell Proliferation Assay Kit (Millipore, USA), as previously described (Karakhanova et al 2014b). At least three independent experiments were performed for each assay.…”
Section: Cell Viability and Proliferation Assaysmentioning
confidence: 99%
See 3 more Smart Citations